Oxidative DNA Damage Accelerates Skin Inflammation in Pristane-Induced Lupus Model - Tumurkhuu, Gantsetseg; Chen, Shuang; Montano, Erica N.; Ercan Laguna, Duygu; De Los Santos, Gabriela; Yu, Jeong Min; Lane, Malcolm; Yamashita, Michifumi; Markman, Janet L.; Blanco, Luz P.; Kaplan, Mariana J.; Shimada, Kenichi; et al. (Frontiers in Immunology, 2020)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory autoimmune disease in which type I interferons (IFN) play a key role. The IFN response can be triggered when oxidized DNA engages the cytosolic DNA sensing platform cGAS-STING, but the repair mechanisms that modulate this process and govern disease progression are unclear. To gain insight into this biology, we interrogated the role of oxyguanine glycosylase 1 (OGG1), which repairs oxidized guanine 8-Oxo-2′-deoxyguanosine (8-OH-dG), in the pristane-induced mouse model of SLE. Ogg1-/- mice showed increased influx of Ly6Chi monocytes into the peritoneal cavity and enhanced IFN-driven gene expression in response to short-term exposure to pristane. Loss of Ogg1 was associated with increased auto-antibodies (anti-dsDNA and anti-RNP), higher total IgG, and higher splenic cell number in response to longer exposure to pristane, accompanied by aggravated skin pathology such as hair loss, thicker epidermis, and increased deposition of IgG in skin lesions. Supporting a role for type I IFNs in this model, skin lesions of Ogg1-/- mice had significantly higher expression of type I IFN genes (ISG-15; IRF-9 and IFNβ). In keeping with loss of Ogg1 resulting in dysregulated IFN responses, enhanced basal and cGAMP-dependent IFNβ expression was observed in Ogg1-/- BMDMs from Ogg1-/- mice. Use of the STING inhibitor, H151, reduced both basal and cGAMP-driven increases, indicating that OGG1 regulates IFNβ expression through the cGAS-STING pathway. Finally, in support for a role for Ogg1 in the pathology of cutaneous disease, reduced OGG1 expression in monocytes associated with skin involvement in SLE patients and the expression of OGG1 was significantly lower in lesional skin compared with non-lesional skin in patients with Discoid Lupus. Taken together, these data support an important role for OGG1 in protecting against IFN production and SLE skin disease.